Association of iron and nutritional status with sleep quality in adolescent girls: A cross-sectional study - Alika Shobrina Hanif; Ani Margawati; Nuryanto Nuryanto (AcTion: Aceh Nutrition Journal, 2026)
Adolescent girls tend to have a higher risk of anemia because their nutritional demands increase during growth and the onset of menstruation. Both anemia and nutritional status have been proposed to affect sleep quality through various physiological pathways. Therefore, this study was designed to examine the relationship between ferritin and hemoglobin levels and nutritional status and how these factors are associated with sleep quality among adolescent girls. A cross-sectional study will be conducted in April–May 2025 with a total of 80 participants from Pekalongan Regency. Information on sleep quality was obtained using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, ferritin levels were examined using the Enzyme-Linked Immunosorbent Assay (ELISA), and hemoglobin levels were assessed using a hematology analyzer. To explore the relationships among ferritin levels, hemoglobin, and nutritional status with sleep quality, a multivariate regression analysis was employed. Bivariate analysis revealed that hemoglobin levels (p= 0.005) and nutritional status (p= 0.007) were significantly associated with sleep quality, whereas ferritin levels were not (p= 0.054). In the multivariate analysis, only hemoglobin level was significantly associated with sleep quality (p < 0.001). These results indicate that lower hemoglobin levels may play a role in worsening sleep quality among adolescent girls, underscoring the need to promote anemia prevention through enhanced nutritional intake.